Seawater degradable cellulose acetate as well as preparation method and application thereof

By preparing seawater, the degradable cellulose acetate is controlled by using a multi-step process to control its structural characteristics, which solves the problem of slow degradation of existing cellulose acetate in seawater, and achieves efficient degradation and excellent performance.

CN119798467APending Publication Date: 2025-04-11SICHUAN PUSH CELLULOSE ACETATE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510001996.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing cellulose acetate products cannot be effectively degraded in seawater environments, making it difficult to solve the problem of marine pollution.

Method used

By preparing a seawater degradable cellulose acetate, the binding sulfonic acid group content and substitution degree of cellulose acetate are controlled by the steps of activation, esterification, structural regulation, relay hydrolysis, precipitation and curing, and post-treatment, and the degradation performance of cellulose acetate is improved.

Benefits of technology

It achieves efficient degradation of cellulose acetate in seawater, with a degradation rate of more than 90%, while maintaining excellent melt processing effect and performance, and is suitable for a variety of fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798467A_ABST
    Figure CN119798467A_ABST
Patent Text Reader

Abstract

The invention discloses seawater degradable cellulose acetate as well as a preparation method and application thereof, and belongs to the technical field of cellulose. The invention discloses cellulose acetate with seawater degradability. A preparation method of the cellulose acetate comprises the following steps: activating; performing esterification; regulating and controlling the structure; carrying out relay hydrolysis; precipitating and curing; carrying out post-treatment; the structure regulation comprises the following steps: adding acetic acid and sulfuric acid into an esterified system, adding water after preliminary hydrolysis, and simultaneously raising the temperature by 5-40 DEG C to regulate the structure for 5-80 minutes; and the relay hydrolysis comprises the following steps: supplementing acetic acid and sulfuric acid, and performing relay hydrolysis for 210-300 minutes. According to the preparation method, after esterification liquid is hydrolyzed to a certain degree, regulation and control of the content of combined sulfonic groups are realized by controlling the water content and increasing the temperature and the time degree, and the substitution degree is reduced by adopting relay hydrolysis, so that the product has excellent seawater degradability; in addition, metal salt and metal oxide can be introduced, and a plasticizer is adopted for granulation, so that the product performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cellulose, and in particular relates to seawater-degradable cellulose acetate and a preparation method and application thereof. Background Art

[0002] Cellulose acetate is a product made from natural cellulose such as cotton linter pulp, bamboo pulp or wood pulp as the main raw material, in which the hydroxyl groups on the cellulose molecular chain are replaced by acetyl groups. The degree to which the hydroxyl groups are replaced is called the degree of substitution, and it is divided into triacetyl cellulose and diacetyl cellulose according to the degree of substitution. The existing large-scale production process of cellulose acetate is to use wood pulp or cotton linter pulp and acetic anhydride for esterification reaction in the presence of solvent (acetic acid or dichloromethane) and catalyst (such as sulfuric acid), and adjust the degree of substitution through saponification (hydrolysis); then after molding, washing, dehydration, drying and other processes, cellulose acetate flakes or particles are obtained. In recent years, with people's attention to the degradation performance of the product, the research on the degradation mechanism of cellulose acetate and how to improve the degradation rate of composting is relatively comprehensive. Its degradation mechanism is generally believed to be divided into three steps: first, acetyl esterase (AE) deacetylates cellulose acetate, then endoglucanase (EG) degrades the glycosidic bonds of the non-reducing ends of long-chain cellulose, and finally, under the action of exoglucanase (CBH) and β-glucosidase (BG), the long-chain polysaccharides are converted into oligosaccharides and finally converted into CO2 and H2O, thereby achieving complete degradation. Based on this degradation mechanism, US20220267574A1 discloses a method for adjusting the degree of substitution distribution, which accelerates the biodegradation rate by increasing the proportion of acetyl groups at the C2 and C3 positions. US005804296A discloses a method for accelerating the degradation rate of cellulose acetate fibers using high specific surface area titanium dioxide as a photocatalyst.

[0003] Plastic waste has had a lasting impact on the earth's natural environment and circulation system, profoundly changing the marine and soil ecosystems, and posing a major threat to the reproduction and survival of organisms, including humans. By 2040, it is estimated that 710 million tons of plastic waste will be generated annually worldwide, and 29 million tons of plastic will flow into the ocean, with 100 kilograms of plastic waste for every meter of coastline. Plastic waste in the ocean will enter the marine ecosystem in the form of microplastics, ultimately affecting the health of all mankind.

[0004] For the above reasons, the seawater degradation performance of materials has also been paid attention to by global researchers as a hot topic in material development. Cellulose acetate is widely used in glasses, cigarette filters, clothing, and cosmetics as plastics, textiles, and microspheres. As they are discarded after use, some products are directly or indirectly carried into the marine environment. Although cellulose acetate can be degraded by composting, photodegradation, or chemical degradation through adjustment of substitution degree, product form design, and formula design, the existing technology cannot make cellulose acetate degradable by seawater. However, at present, the degradation performance of all commercial cellulose acetate products cannot be adjusted, and it is impossible to achieve "land and sea degradation". The reason is that compared with composting degradation, the marine environment has a low temperature and few specific microorganisms, which leads to slow initial degradation of cellulose acetate. In order to achieve seawater degradation of products, it is necessary not only to consider the feasibility of the process, controllable quality, and cost considerations, but also to comprehensively consider whether it has commercial application value, that is, to achieve coordinated regulation of degradation performance and use performance.

[0005] Therefore, it is of great significance to study or develop a seawater-degradable cellulose acetate that meets these requirements. Summary of the invention

[0006] The purpose of the present invention is to develop a cellulose acetate which is degradable in seawater, while ensuring low production cost and coordinated regulation of degradation performance and use performance.

[0007] To achieve the above object, the present invention first provides a method for preparing seawater-degradable cellulose acetate, which comprises the following steps: A. activation: using 100 parts by weight of pulp as raw material; B. esterification; C. structure regulation; D. relay hydrolysis; E. precipitation and solidification; F. post-treatment to obtain cellulose acetate;

[0008] Wherein, step C, structure regulation specifically comprises: adding glacial acetic acid and sulfuric acid to the esterified system for preliminary hydrolysis, then adding 20 to 40 parts by weight of water to the system, while raising the system temperature by 5 to 40° C., and performing structure regulation for 5 to 80 minutes;

[0009] Step D, relay hydrolysis is specifically as follows: after the structure control is completed, 5 to 15 parts by weight of glacial acetic acid and 0.2 to 1.0 parts by weight of sulfuric acid are added to the system, the temperature is controlled to be not less than 60° C., and the relay hydrolysis is performed for 210 to 300 minutes, and then the remaining sulfuric acid in the slurry is neutralized to terminate the hydrolysis reaction.

[0010] Wherein, in the above preparation method, in step C, the amount of glacial acetic acid added is 10 to 30 parts by weight.

[0011] Wherein, in the above preparation method, in step C, the amount of sulfuric acid added is 1 to 3 parts by weight.

[0012] Wherein, in the above preparation method, in step C, the temperature of the initial hydrolysis is 50-70°C.

[0013] Wherein, in the above preparation method, in step C, the time of the initial hydrolysis is 240 to 360 minutes.

[0014] Preferably, in the above preparation method, in step C, the system temperature is increased by 8 to 15°C.

[0015] Preferably, in the above preparation method, in step C, the structure regulation is performed for 10 to 30 minutes.

[0016] Preferably, in the above preparation method, in step D, 0.5 to 0.8 parts by weight of sulfuric acid is added.

[0017] Wherein, in the above preparation method, in step D, the temperature is controlled at 60-80°C.

[0018] Preferably, in the above preparation method, in step D, the relay hydrolysis is carried out for 230 to 280 minutes.

[0019] Wherein, in the above preparation method, in step D, the operation of neutralizing the remaining sulfuric acid in the slurry is: adding 3 to 5 parts by weight of glacial acetic acid and 15 to 20 parts by weight of a 10 to 15% carbonate aqueous solution to the system.

[0020] Among them, in the above preparation method, step A, activation is specifically: after the pulp and glacial acetic acid are fully mixed, glacial acetic acid and sulfuric acid are added, and the temperature and time are controlled to perform activation.

[0021] Preferably, in the above preparation method, step A, activation is specifically as follows: after 100 parts by weight of pulp and 200-400 parts by weight of glacial acetic acid are fully mixed, 100-300 parts by weight of glacial acetic acid and 0.2-1 parts by weight of sulfuric acid are added, the temperature is controlled not to exceed 40° C., and activation is performed for 60-180 minutes.

[0022] Among them, in the above preparation method, step B, esterification is specifically: adding acetic anhydride and sulfuric acid to the activated system, controlling the temperature not to exceed 80°C, carrying out esterification, and then adding water to terminate the esterification reaction.

[0023] Preferably, in the above preparation method, step B, esterification is specifically as follows: 300 to 500 parts by weight of acetic anhydride and 0.2 to 1 parts by weight of sulfuric acid are added to the activated system, the temperature is controlled not to exceed 80°C, and esterification is carried out until the appearance of the system gradually changes to a transparent colloid, and then 60 to 100 parts by weight of water are added to terminate the esterification reaction.

[0024] In the above preparation method, step E, precipitation and solidification, specifically comprises: after the relay hydrolysis is completed, filtering the system slurry, and then mixing the filtrate with water, stirring, precipitating and solidifying.

[0025] Preferably, in the above preparation method, step E, precipitation and solidification are specifically as follows: after the relay hydrolysis is completed, the system slurry is filtered, and then the filtrate temperature is reduced to 10-30°C, mixed with low-temperature water of 2-10°C, stirred, precipitated and solidified.

[0026] Among them, in the above preparation method, step F, post-treatment is specifically: washing the solidified material with water until it is neutral, draining and drying, to obtain cellulose acetate.

[0027] Preferably, in the above preparation method, step F, post-treatment is specifically as follows: washing the solidified material with water until it is neutral, draining and drying it, and then grinding it to a particle size not exceeding 500 μm to obtain cellulose acetate powder.

[0028] In the post-processing step, the metal salt M is introduced x A y and / or metal oxide M z O w (Using the method in ZL201811009739.3 or a similar method), improve product stability and improve the seawater degradation ability of cellulose acetate. In the above preparation method, step F also includes introducing a metal salt M x A y and / or metal oxide M z O w Operation; M x A y is a carbonate, bicarbonate or hydrochloride formed by any one of magnesium ion, calcium ion or barium ion, M x A y pK b The value is 3.7~7.6; M z O w An oxide formed by any one of magnesium, calcium or barium;

[0029] Step F, post-treatment is specifically: washing the solidified material with water to neutrality, introducing metal salt M x A y and / or metal oxide M z O w After draining and drying, cellulose acetate is obtained; the metal salt M is introduced x A y and / or metal oxide M z O w The method is: a. Soaking: Soak the washed neutral material in the metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt Mx A y and metal oxide M z O w or, b. washing: washing the neutralized material with a metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt M x A y and metal oxide M z O w Mix the aqueous solutions for washing.

[0030] Preferably, in the above preparation method, in step F, the metal salt M x A y At least one selected from magnesium carbonate, calcium carbonate, barium carbonate, magnesium bicarbonate, calcium bicarbonate or barium bicarbonate.

[0031] More preferably, in the above preparation method, in step F, the metal salt M x A y At least one selected from magnesium carbonate or magnesium bicarbonate.

[0032] Preferably, in the above preparation method, in step F, the metal oxide M z O w At least one selected from magnesium oxide, calcium oxide or barium oxide.

[0033] More preferably, in the above preparation method, in step F, the metal oxide M z O w Selected from magnesium oxide.

[0034] Wherein, in the above preparation method, in step F, the metal salt M x A y The mass concentration of the aqueous solution is 10-40%, and the metal oxide M z O w The mass concentration of the aqueous solution is 10-40%, and the metal salt M x A y and metal oxide M z O w The mass concentration of the mixed aqueous solution is 10-40%.

[0035] Wherein, in the above preparation method, in step F, when the immersion method is adopted, the metal salt M in each aqueous solution is controlled x A y and metal oxide M z O w The total addition amount is 0.1 to 1.0 parts by weight.

[0036] Preferably, in the above preparation method, in step F, when the immersion method is adopted, the metal salt M in each aqueous solution is controlled x A y and metal oxide M z O w The total addition amount is 0.1 to 0.5 parts by weight.

[0037] Wherein, in the above preparation method, in step F, when the immersion method is adopted, the immersion time is not less than 5 minutes.

[0038] Wherein, in the above preparation method, in step F, when the washing method is adopted, the amount of each aqueous solution used is 0.5 to 5 parts by weight.

[0039] Preferably, in the above preparation method, in step F, cellulose acetate is ground to a particle size not exceeding 500 μm to obtain cellulose acetate powder.

[0040] The present invention selects a plasticizer, especially a hydrophilic plasticizer, to further increase the degradation rate of plastic products in seawater. The above preparation method further includes step G:

[0041] Step G, melt processing: the cellulose acetate powder and the plasticizer are mixed evenly and fully plasticized, and then melt-extruded and granulated to obtain cellulose acetate granules.

[0042] Wherein, in the above preparation method, in step G, the plasticizer is at least one of o-phthalates, glycerol lipids, citrate esters or polymerized polyols.

[0043] Preferably, in the above preparation method, in step G, the plasticizer is at least one of glycerol lipids, citrate esters or polymerized polyols.

[0044] More preferably, in the above preparation method, in step G, the plasticizer is at least one of triethyl citrate, triacetin or PEG400.

[0045] Wherein, in the above preparation method, in step G, the amount of the plasticizer added is 20 to 40 parts by weight.

[0046] Wherein, in the above preparation method, in step G, the temperature of the melt extrusion granulation is set as follows: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0047] The present invention also provides a seawater-degradable cellulose acetate, which is prepared by the above-mentioned preparation method. When the fully esterified cellulose acetate stock solution is hydrolyzed to a certain degree of substitution, the water content in the system is regulated and the system temperature is rapidly increased, thereby achieving the regulation of the content of bound sulfonic acid groups. After the structure regulation is completed, a catalyst is added again to maintain the hydrolysis reaction rate, so that the bound sulfonic acid group content of the seawater-degradable cellulose acetate is 20-200 ppm and the degree of substitution is 1.6-2.2.

[0048] To further improve product performance, preferably, the seawater-degradable cellulose acetate has a combined sulfonic acid group content of 80 to 150 ppm and a degree of substitution of 1.7 to 2.0.

[0049] The cellulose acetate of the present invention has excellent seawater degradability, and also has excellent melt processing effect and use performance, and can be widely used in various fields. Therefore, the present invention also provides the use of the above-mentioned seawater degradable cellulose acetate prepared by the above-mentioned preparation method or in textiles, cigarette filters, cosmetics, eyeglass frames, packaging, cutlery, tool handles or medical drugs.

[0050] In the present invention, the sulfuric acid used is conventional commercially available concentrated sulfuric acid, and its mass concentration is about 98%.

[0051] Beneficial effects of the present invention:

[0052] The present invention performs structural regulation on the activated and esterified cellulose. When the fully esterified cellulose acetate stock solution is hydrolyzed to a certain degree of substitution, the water content in the system is regulated, and the system temperature is rapidly increased. By controlling the water content, the temperature increase and the time, the regulation of the content of the bound sulfonic acid groups is achieved, and a certain amount of sulfonic acid groups are retained in the cellulose acetate, so that it has seawater degradability. Then, in the same reaction system, after the structural regulation is completed, the present invention removes a certain amount of bound sulfonic acid groups, and then adds a catalyst again to maintain the hydrolysis reaction rate, and adopts relay hydrolysis to reduce the degree of substitution, so that the degree of substitution of the cellulose acetate is controlled within an appropriate range, and its seawater degradability is further guaranteed.

[0053] The present invention can also introduce weakly alkaline metal salts in the post-processing process, control the type and amount of metal salts, improve product stability, and improve the seawater degradation ability of cellulose acetate in a targeted manner. In addition, the present invention can also select hydrophilic plasticizers to further increase the seawater degradation rate of plastic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 The schematic diagram of the production of cellulose acetate combined with sulfonic acid groups of the present invention. DETAILED DESCRIPTION

[0055] Specifically, a method for preparing seawater-degradable cellulose acetate comprises the following steps: A. activation: using 100 parts by weight of pulp as a raw material; B. esterification; C. structural regulation; D. relay hydrolysis; E. precipitation and solidification; F. post-treatment to obtain cellulose acetate;

[0056] Wherein, step C, structure regulation specifically comprises: adding glacial acetic acid and sulfuric acid to the esterified system for preliminary hydrolysis, then adding 20 to 40 parts by weight of water to the system, while raising the system temperature by 5 to 40° C., and performing structure regulation for 5 to 80 minutes;

[0057] Step D, relay hydrolysis is specifically as follows: after the structure control is completed, 5 to 15 parts by weight of glacial acetic acid and 0.2 to 1.0 parts by weight of sulfuric acid are added to the system, the temperature is controlled to be not less than 60° C., and the relay hydrolysis is performed for 210 to 300 minutes, and then the remaining sulfuric acid in the slurry is neutralized to terminate the hydrolysis reaction.

[0058] At present, almost all commercial cellulose acetate is produced using acetic acid as a solvent, acetic anhydride as an acetylating agent, and sulfuric acid as a catalyst. During the production process, cellulose and sulfuric acid undergo a sulfonation reaction, and some acetylated groups are replaced by sulfonic acid groups, thereby forming a bonded sulfonic acid group on the cellulose acetate molecular structure (see Figure 1 , Figure 1 Only the principle of cellulose acetate combined with sulfonic acid groups is shown. The main reaction is still that cellulose is converted into triacetyl cellulose through esterification reaction, and triacetyl cellulose is converted into diacetyl cellulose through hydrolysis. Therefore, the sulfonic acid group content in the cellulose acetate of the present invention is still very small). These combined sulfonic acid groups will affect the performance of cellulose acetate products. Whether it is used as a tow or a plastic, it is not allowed. Therefore, in the traditional production process, they are effectively removed through esterification and hydrolysis steps. For example, in the preparation process of cellulose acetate, CN108948214A uses metal salts as terminators for hydrolysis reactions or neutralizers for washing steps to improve the stability of its products, but it still needs to remove the combined sulfonic acid groups, so its products do not have the function of being degradable by seawater.

[0059] However, for seawater degradable products, if the number of bound sulfonic acid groups is effectively controlled (i.e., a certain amount is retained), free sulfate ions and hydrogen ions can be quickly provided during the material degradation process, thereby improving the initial degradation ability of the material in the seawater environment, and providing the possibility for the degradability of the material in the seawater environment. Based on the above findings, the present invention adjusts the content of sulfonic acid groups in cellulose acetate by structural regulation in step C.

[0060] In step C of the present invention, the preliminary hydrolysis is a conventional operation in the art. During the preliminary hydrolysis, the amount of glacial acetic acid added is 10 to 30 parts by weight, the amount of sulfuric acid added is 1 to 3 parts by weight, the temperature of the preliminary hydrolysis is 50 to 70° C., and the time of the preliminary hydrolysis is 240 to 360 minutes.

[0061] After the slurry is initially hydrolyzed for a certain period of time, the system temperature is controlled by high-temperature heating to achieve the production of cellulose acetate with different contents of bound sulfonic acid groups. In step C of the present invention, the structural regulation mainly regulates the content of bound sulfonic acid groups, which is achieved by increasing the temperature, and water is added to prepare for further relay hydrolysis. In the regulation stage, the higher the temperature increase and the longer the time, the greater the removal of the sulfonic acid group content. Therefore, the present invention needs to control the temperature increase and time to control the retention of a certain amount of sulfonic acid groups in the cellulose acetate. In order to further control the sulfonic acid group content within a reasonable range and further improve the product performance, preferably, in step C, the system temperature is increased by 8 to 15°C, and the structural regulation is performed for 10 to 30 minutes.

[0062] In addition to the sulfonic acid content, the degree of substitution range is also a key indicator requirement for the product of the present invention to achieve seawater degradation. In the relay hydrolysis of step D of the present invention, by adding acetic acid and sulfuric acid, and removing certain bound sulfonic acid groups, a deeper hydrolysis is performed, so that the degree of substitution reaches a lower level, and the cost is greatly reduced through the relay hydrolysis method, and production is feasible. Preferably, in step D, 0.5 to 0.8 parts by weight of sulfuric acid is added. In step D, the temperature of the relay hydrolysis is lower than the temperature during the structural adjustment, and the temperature is generally controlled at 60 to 80°C.

[0063] In step D of the present invention, the operation of neutralizing the residual sulfuric acid in the slurry is: adding 3 to 5 parts by weight of glacial acetic acid and 15 to 20 parts by weight of a carbonate aqueous solution with a mass concentration of 10 to 15% to the system. The purpose of adding glacial acetic acid and carbonate is to neutralize the sulfuric acid in the slurry. After reaction and post-treatment, these salts added at this time will basically not remain. However, the present invention is not limited to the method of adding acetic acid and carbonate aqueous solution to neutralize the residual sulfuric acid in the slurry. As long as the added materials can neutralize the residual sulfuric acid and do not affect the product performance, they are applicable to the method of the present invention.

[0064] In order to further control the degree of substitution within a reasonable range and further improve product performance, preferably, in step D, the relay hydrolysis is carried out for 230 to 280 minutes.

[0065] In the present invention, step A, activation is a conventional operation in the art, and step A, activation specifically comprises: after pulp and glacial acetic acid are fully mixed, glacial acetic acid and sulfuric acid are added, and the temperature and time are controlled to activate. Preferably, step A, activation specifically comprises: after 100 parts by weight of pulp and 200-400 parts by weight of glacial acetic acid are fully mixed, 100-300 parts by weight of glacial acetic acid and 0.2-1 parts by weight of sulfuric acid are added, the temperature is controlled not to exceed 40° C., and activation is performed for 60-180 minutes.

[0066] In the present invention, step B, esterification is a conventional operation in the art, and step B, esterification is specifically: add acetic anhydride and sulfuric acid to the activated system, control the temperature not to exceed 80°C, carry out esterification, and then add water to terminate the esterification reaction. Preferably, step B, esterification is specifically: add 300-500 parts by weight of acetic anhydride and 0.2-1 parts by weight of sulfuric acid to the activated system, control the temperature not to exceed 80°C, carry out esterification until the appearance of the system gradually changes to a transparent colloid, and then add 60-100 parts by weight of water to terminate the esterification reaction. In step B of the present invention, only after the acetic anhydride in the system is reacted, water may exist in the system, and the possibility of hydrolysis in the next step is available.

[0067] In the present invention, step E, precipitation and solidification are conventional operations in the art, and step E, precipitation and solidification are specifically as follows: after the relay hydrolysis is completed, the system slurry is filtered, and then the filtrate is mixed with water, stirred, precipitated and solidified. Preferably, step E, precipitation and solidification are specifically as follows: after the relay hydrolysis is completed, the system slurry is filtered, and then the filtrate temperature is reduced to 10-30°C, and mixed with low-temperature water of 2-10°C, stirred, precipitated and solidified.

[0068] The step F of the present invention, post-treatment, can be performed by conventional operations in the art. In this case, the step F, post-treatment is specifically as follows: washing the solidified material with water until it is neutral, draining and drying, and obtaining cellulose acetate. Preferably, in this case, the step F, post-treatment is specifically as follows: washing the solidified material with water until it is neutral, draining and drying, and grinding it to a particle size of no more than 500 μm to obtain cellulose acetate powder.

[0069] In order to further improve the product performance, the present invention introduces metal salt M in the post-treatment process. x A y and / or metal oxide M z O w , improve product stability, and improve the seawater degradation ability of cellulose acetate. At this time, step F also includes introducing a metal salt M x A y and / or metal oxide M z O w Operation; M x A yis a carbonate, bicarbonate or hydrochloride formed by any one of magnesium ion, calcium ion or barium ion, M x A y pK b The value is 3.7~7.6; M z O w An oxide formed by any one of magnesium, calcium or barium;

[0070] Step F, post-treatment is specifically: washing the solidified material with water to neutrality, introducing metal salt M x A y and / or metal oxide M z O w After draining and drying, cellulose acetate is obtained; the metal salt M is introduced x A y and / or metal oxide M z O w The method is: a. Soaking: Soak the washed neutral material in the metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt M x A y and metal oxide M z O w or, b. washing: washing the neutralized material with a metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt M x A y and metal oxide M z O w Mix the aqueous solutions for washing.

[0071] To further improve product performance, preferably, in step F, the metal salt M x A y At least one selected from magnesium carbonate, calcium carbonate, barium carbonate, magnesium bicarbonate, calcium bicarbonate or barium bicarbonate. More preferably, in step F, the metal salt M x A y At least one selected from magnesium carbonate or magnesium bicarbonate.

[0072] To further improve product performance, preferably, in step F, the metal oxide M z O w At least one of magnesium oxide, calcium oxide or barium oxide is selected. More preferably, in step F, the metal oxide M z O w Selected from magnesium oxide.

[0073] In step F of the present invention, the metal salt M x A y The mass concentration of the aqueous solution is 10-40%, and the metal oxide M z O w The mass concentration of the aqueous solution is 10-40%, and the metal salt M x A y and metal oxide M z O w The mass concentration of the mixed aqueous solution is 10-40%.

[0074] In step F of the present invention, when the immersion method is adopted, the metal salt M in each aqueous solution is controlled x A y and metal oxide M z O w The total amount of the metal salt M in each aqueous solution is controlled to be 0.1 to 1.0 parts by weight. x A y and metal oxide M z O w The total amount of the added is 0.1 to 0.5 parts by weight. When the immersion method is adopted, the immersion time is not less than 5 minutes.

[0075] In step F of the present invention, when washing is adopted, the amount of each aqueous solution used is 0.5 to 5 parts by weight.

[0076] In step F of the present invention, cellulose acetate is ground to a particle size not exceeding 500 μm to obtain cellulose acetate powder.

[0077] The present invention selects a plasticizer, especially a hydrophilic plasticizer, to further increase the degradation rate of plastic products in seawater. Therefore, the preparation method of the present invention also includes step G:

[0078] Step G, melt processing: the cellulose acetate powder and the plasticizer are mixed evenly and fully plasticized, and then melt-extruded and granulated to obtain cellulose acetate granules.

[0079] In step G of the present invention, the plasticizer may be a commonly used plasticizer in the art, such as at least one of phthalates, glycerol lipids, citrates or polymerized polyols. It has been found through experiments that non-hydrophilic plasticizers such as DEP have a weaker degradation-promoting effect than hydrophilic plasticizers. Therefore, in order to further improve product performance, preferably, in step G, the plasticizer is at least one of glycerol lipids, citrates or polymerized polyols. In order to further improve product performance, more preferably, in step G, the plasticizer is at least one of triethyl citrate, triacetin or PEG400.

[0080] In step G of the present invention, the amount of the plasticizer added is 20 to 40 parts by weight.

[0081] In step G of the present invention, the temperature of the melt extrusion granulation is set as follows: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0082] The present invention also provides a seawater-degradable cellulose acetate, which is prepared by the above-mentioned preparation method. When the fully esterified cellulose acetate stock solution is hydrolyzed to a certain degree of substitution, the water content in the system is regulated and the system temperature is rapidly increased, thereby achieving the regulation of the content of bound sulfonic acid groups. After the structure regulation is completed, a catalyst is added again to maintain the hydrolysis reaction rate, so that the bound sulfonic acid group content of the seawater-degradable cellulose acetate is 20-200 ppm and the degree of substitution is 1.6-2.2.

[0083] To further improve product performance, preferably, the combined sulfonic acid content of the seawater degradable cellulose acetate is 80-150 ppm, and the degree of substitution is 1.7-2.0. When the combined sulfonic acid content is higher than 300 ppm, the product performance is poor and has no practical value; when the degree of substitution is greater than 2.4, its seawater degradability is poor; when the degree of substitution is lower than 1.6, the content of acetone insoluble matter in the product is high, its melt processing ability is poor, and it has no market application value.

[0084] The cellulose acetate of the present invention has excellent seawater degradability, and also has excellent melt processing effect and use performance, and can be widely used in various fields. Therefore, the present invention also provides the use of the above-mentioned seawater degradable cellulose acetate prepared by the above-mentioned preparation method or in textiles, cigarette filters, cosmetics, eyeglass frames, packaging, cutlery, tool handles or medical drugs.

[0085] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the scope of the examples.

[0086] Degree of substitution test:

[0087] The combined acid value was measured according to Appendix A of GB / T 32117-2015 "Industrial Cellulose Diacetate Sheet", and the degree of substitution was calculated according to the following formula.

[0088] DS = 162*CAA / (6000-42*CAA); wherein DS is the degree of substitution and CAA is the combined acid value.

[0089] Combined sulfonic acid test:

[0090] According to the sulfonic acid group test method in Appendix A of ASTM D871 "Standard Test Method for Cellulose Acetate", the sample is pretreated to remove free sulfate ions. The treated cellulose acetate is then placed in a dilute hydrochloric acid (1:1) solution and mixed thoroughly, then placed under high temperature and high pressure for hydrolysis to release the bound sulfonic acid groups. After filtration, the bound sulfonic acid groups are converted into sulfates and exist in the water. Anti-interference agents and excess barium chloride solution are added and shaken thoroughly. The solution is then placed in a spectrophotometer cuvette, and the bound sulfonic acid group content is measured using a pre-established standard curve, expressed as HSO3 - Indicated by unit ppm.

[0091] Seawater degradation performance test:

[0092] Sample preparation: For cellulose acetate powder products, dissolve the powder in acetone / water (95 / 5w / w) solution at a concentration of 20%. After fully dissolved, evenly apply it on a coating machine into a 0.1mm thick film. After the acetone evaporates, a transparent film sample is obtained for seawater degradation testing. For plasticized cellulose acetate granule products, a disc sample with a diameter of 45mm and a thickness of 2mm is made for seawater degradation testing. Wrap the diaphragm or disc with a metal 300-mesh stainless steel filter and place it in pre-configured artificial simulated seawater for degradation. Take out the metal filter and disc every 30 days, test the weight after sufficient drying, and calculate the seawater degradation rate. The calculation formula is as follows:

[0093] Seawater degradation rate L x =(W X -W0) / W0;

[0094] L: weight loss rate, X: degradation days, W x : The weight of the disc after degradation for X days, W0: represents the weight of the original disc before the degradation test begins.

[0095] Preparation method of artificial seawater: Dissolve 22g sodium chloride (NaCl), 9.7g magnesium chloride hexahydrate (MgCl2·6H20), 3.7g sodium sulfate (Na2SO4), 1g calcium chloride (CaCl2), 0.65g potassium chloride (KCl), and 0.20g sodium bicarbonate (NaHCO3) in water and make up to 1000mL.

[0096] Example 1

[0097] S1 Activation: 100 parts by weight of pulp crushed into fluff and 300 parts by weight of glacial acetic acid are added into a stirred reactor for thorough mixing, and then 200 parts by weight of glacial acetic acid and 0.3 parts by weight of sulfuric acid are added for activation. The activation temperature and time are controlled, and the activation time is 120 minutes at a temperature below 40°C.

[0098] S2 esterification: After activation, add a mixed solution of 400 parts by weight of acetic anhydride and 0.3 parts by weight of sulfuric acid to the system. At this time, acetic anhydride begins to react with water, and the system temperature rises instantly. When the water in the system has finished reacting, acetic anhydride begins to react with cellulose, and the system temperature rises slowly again. The temperature of the reaction system is controlled not to exceed 80°C until the appearance of the system gradually changes to a transparent colloid, and then 80 parts by weight of water are added to react with the remaining acetic anhydride, thereby terminating the esterification reaction.

[0099] S3 structure regulation: add 20 parts by weight of glacial acetic acid and 1.5 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 30°C for structure regulation for 60 minutes.

[0100] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 240 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0101] S5 precipitation and solidification: After filtering, the slurry is cooled to 10-30℃, mixed with low-temperature water at 2-10℃ and fed into the molding machine for full stirring, precipitation and solidification.

[0102] S6 post-treatment: Use water to fully wash the solidified material until it is neutral. Drain and dry to obtain cellulose acetate product, and then grind the product into cellulose acetate powder less than 500 μm.

[0103] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0104] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0105] Example 2

[0106] S1-S2 are the same as in Example 1.

[0107] S3 structure regulation: add 20 parts by weight of glacial acetic acid and 1.5 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 15°C for structure regulation for 40 minutes.

[0108] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 240 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0109] S5-S7 are the same as in Example 1.

[0110] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0111] Example 3

[0112] S1-S2 are the same as in Example 1.

[0113] S3 structure regulation: add 20 parts by weight of glacial acetic acid and 1.5 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 10°C for structure regulation for 20 minutes.

[0114] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 240 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0115] S5-S7 are the same as in Example 1.

[0116] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0117] Example 4

[0118] S1-S2 are the same as in Example 1.

[0119] S3 structure control: add 20 parts by weight of glacial acetic acid and 1.5 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, do not increase the temperature, and directly enter the relay hydrolysis step.

[0120] S4 relay hydrolysis: 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 240 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0121] S5-S7 are the same as in Example 1.

[0122] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0123] Example 5

[0124] S1-S2 are the same as in Example 1.

[0125] S3 structure regulation: add 20 parts by weight of glacial acetic acid and 1.8 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 10°C for structure regulation for 20 minutes.

[0126] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, and the temperature is controlled to be not less than 60°C. After 180 minutes of relay hydrolysis, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0127] S5-S7 are the same as in Example 1.

[0128] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0129] Example 6

[0130] S1-S2 are the same as in Example 1.

[0131] S3 is the same as Example 5.

[0132] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 210 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0133] S5-S7 are the same as in Example 1.

[0134] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0135] Example 7

[0136] S1-S2 are the same as in Example 1.

[0137] S3 is the same as Example 5.

[0138] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 240 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0139] S5-S7 are the same as in Example 1.

[0140] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0141] Example 8

[0142] S1-S2 are the same as in Example 1.

[0143] S3 is the same as Example 5.

[0144] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.5 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 300 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0145] S5-S7 are the same as in Example 1.

[0146] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0147] Example 9

[0148] S1-S2 are the same as in Example 1.

[0149] S3 structure regulation: add 20 parts by weight of glacial acetic acid and 2.0 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 300 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 10°C for structure regulation for 20 minutes.

[0150] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.6 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 270 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0151] S5 precipitation and solidification: After filtering, the slurry is cooled to 10-30℃, mixed with low-temperature water at 2-10℃ and fed into the molding machine for full stirring, precipitation and solidification.

[0152] S6 post-treatment: The solidified material is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.1 parts by weight of magnesium carbonate. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0153] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0154] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0155] Example 10

[0156] S1-S2 are the same as in Example 1.

[0157] S3 is the same as Example 9.

[0158] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.7 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 270 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0159] S5 precipitation and solidification: After filtering, the slurry is cooled to 10-30℃, mixed with low-temperature water at 2-10℃ and fed into the molding machine for full stirring, precipitation and solidification.

[0160] S6 post-treatment: The solidified material product is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.3 parts by weight of magnesium carbonate. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0161] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0162] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0163] Embodiment 11

[0164] S1-S2 are the same as in Example 1.

[0165] S3 is the same as Example 9.

[0166] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.8 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 270 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0167] S5 precipitation and solidification: After filtering, the slurry is cooled to 10-30℃, mixed with low-temperature water at 2-10℃ and fed into the molding machine for full stirring, precipitation and solidification.

[0168] S6 post-treatment: The solidified material is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.8 parts by weight of magnesium carbonate. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0169] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0170] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0171] Example 12

[0172] S1-S2 are the same as in Example 1.

[0173] S3 structural adjustment: add 20 parts by weight of glacial acetic acid and 2.2 parts by weight of sulfuric acid to the system of the reactor, keep the temperature at 60°C for hydrolysis for 330 minutes, then add 30 parts by weight of water to the system of the reactor, and quickly raise the system temperature by 10°C for structural adjustment for 20 minutes.

[0174] S4 relay hydrolysis: After the structural regulation is completed, 10 parts by weight of glacial acetic acid and 0.8 parts by weight of sulfuric acid are added to the system of the reactor again, the temperature is controlled to be not less than 60°C, and the relay hydrolysis is carried out for 270 minutes. Then, a mixed solution of glacial acetic acid and potassium carbonate, sodium carbonate, and magnesium carbonate is added to neutralize the remaining sulfuric acid in the slurry and terminate the hydrolysis reaction.

[0175] S5 precipitation and solidification: After filtering, the slurry is cooled to 10-30℃, mixed with low-temperature water at 2-10℃ and fed into the molding machine for full stirring, precipitation and solidification.

[0176] S6 post-treatment: The solidified material is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.2 parts by weight of magnesium carbonate. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0177] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of triethyl citrate (CTE) were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0178] The sulfonic acid content, degree of substitution, and melt processing effect of the cellulose acetate powder of this example were analyzed, and the seawater degradation rate test was performed using S7 to obtain cellulose acetate particles. The results are shown in Table 1.

[0179] Embodiment 13

[0180] S1-S2 are the same as in Example 1.

[0181] S3-S6 are the same as Example 12.

[0182] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of glyceryl triacetate (GTA) were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0183] The sulfonic acid content, degree of substitution, and melt processing effect of the cellulose acetate powder of this example were analyzed, and the seawater degradation rate test was performed using S7 to obtain cellulose acetate particles. The results are shown in Table 1.

[0184] Embodiment 14

[0185] S1-S2 are the same as in Example 1.

[0186] S3-S6 are the same as Example 12.

[0187] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of PEG400 were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0188] The sulfonic acid content, degree of substitution, and melt processing effect of the cellulose acetate powder of this example were analyzed, and the seawater degradation rate test was performed using S7 to obtain cellulose acetate particles. The results are shown in Table 1.

[0189] Embodiment 15

[0190] S1-S2 are the same as in Example 1.

[0191] S3-S6 are the same as Example 12.

[0192] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of PEG800 were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0193] The sulfonic acid content, degree of substitution, and melt processing effect of the cellulose acetate powder of this example were analyzed, and the seawater degradation rate test was performed using S7 to obtain cellulose acetate particles. The results are shown in Table 1.

[0194] Example 16

[0195] S1-S2 are the same as in Example 1.

[0196] S3-S6 are the same as Example 12.

[0197] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0198] The sulfonic acid content, degree of substitution, and melt processing effect of the cellulose acetate powder of this example were analyzed, and the seawater degradation rate test was performed using S7 to obtain cellulose acetate particles. The results are shown in Table 1.

[0199] Embodiment 17

[0200] S1-S2 are the same as in Example 1.

[0201] S3-S5 are the same as Example 12.

[0202] S6 post-treatment: The solidified material is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.2 parts by weight of magnesium oxide. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0203] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0204] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0205] Embodiment 18

[0206] S1-S2 are the same as in Example 1.

[0207] S3-S5 are the same as Example 12.

[0208] S6 Post-treatment: The solidified material is fully washed with water until it is neutral. After washing, the material is immersed in an aqueous solution containing 0.2 parts by weight of calcium carbonate. After draining and drying, the cellulose acetate product is obtained, and then the product is ground into cellulose acetate powder less than 500 μm.

[0209] S7 melt processing evaluation: Cellulose acetate powder and 30 parts by weight of diethyl phthalate were mixed evenly and fully plasticized, and melt extruded and granulated in a twin-screw extruder. Melt extrusion temperature settings: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

[0210] The sulfonic acid group content, degree of substitution, seawater degradation rate, and melt processing effect evaluation of the cellulose acetate powder of this example were analyzed. The results are shown in Table 1.

[0211] Table 1 Performance of the products obtained in the examples

[0212]

[0213]

[0214] Note: In Examples 1-11 and 17-18, the degradation rate of cellulose acetate powder in seawater was analyzed, so the plasticizer was represented by “-”.

[0215] As can be seen from the table, traditional substituted cellulose acetate products are not seawater degradable. Only when the degree of substitution is reduced to below 2.2, the product is seawater degradable. On this basis, the higher the sulfonic acid group, the better the seawater degradability of the product. At the same time, the controlled weak alkaline metal compounds further optimize the seawater degradation performance of the product, and the seawater degradation rate reaches more than 90% in 180 days, meeting the seawater degradation performance requirements, providing a seawater degradable solution for the product in the fields of textiles, cigarette filters, cosmetics, etc. At the same time, in view of the use of cellulose acetate in the plastic field, the seawater degradation performance is maintained by selecting a hydrophilic plasticizer. When a hydrophilic plasticizer such as CTE or PEG400 is selected, the seawater degradation rate reaches more than 90% in 180 days, meeting the seawater degradation performance requirements.

Claims

1. A method for preparing seawater-degradable cellulose acetate, characterized in that: The following steps are involved: A. Activation: 100 parts by weight of pulp as raw material; B. Esterification; C. Structural regulation; D. Relay hydrolysis; E. Precipitation and solidification; F. Post-treatment to obtain cellulose acetate; Wherein, step C, structure regulation specifically comprises: adding glacial acetic acid and sulfuric acid to the esterified system for preliminary hydrolysis, then adding 20 to 40 parts by weight of water to the system, while raising the system temperature by 5 to 40° C., and performing structure regulation for 5 to 80 minutes; Step D, relay hydrolysis is specifically as follows: after the structure control is completed, 5 to 15 parts by weight of glacial acetic acid and 0.2 to 1.0 parts by weight of sulfuric acid are added to the system, the temperature is controlled to be not less than 60° C., and the relay hydrolysis is performed for 210 to 300 minutes, and then the remaining sulfuric acid in the slurry is neutralized to terminate the hydrolysis reaction.

2. The method for preparing seawater-degradable cellulose acetate according to claim 1, characterized in that: At least one of the following is met: In step C, the amount of glacial acetic acid added is 10 to 30 parts by weight; In step C, the amount of sulfuric acid added is 1 to 3 parts by weight; In step C, the temperature of the initial hydrolysis is 50-70°C; In step C, the initial hydrolysis time is 240 to 360 minutes; In step C, the system temperature is increased by 8 to 15°C; In step C, the structure regulation is performed for 10 to 30 minutes.

3. The method for preparing seawater-degradable cellulose acetate according to claim 1, characterized in that: At least one of the following is met: In step D, 0.5 to 0.8 parts by weight of sulfuric acid is added; In step D, the temperature is controlled at 60-80°C; In step D, the relay hydrolysis is carried out for 230 to 280 minutes; In step D, the operation of neutralizing the remaining sulfuric acid in the slurry is: adding 3 to 5 parts by weight of glacial acetic acid and 15 to 20 parts by weight of a carbonate aqueous solution with a mass concentration of 10 to 15% to the system.

4. The method for preparing seawater-degradable cellulose acetate according to claim 1, characterized in that: At least one of the following is met: Step A, activation specifically comprises: after the pulp and glacial acetic acid are fully mixed, glacial acetic acid and sulfuric acid are added, and the temperature and time are controlled to activate; preferably, step A, activation specifically comprises: after 100 parts by weight of pulp and 200-400 parts by weight of glacial acetic acid are fully mixed, 100-300 parts by weight of glacial acetic acid and 0.2-1 parts by weight of sulfuric acid are added, the temperature is controlled not to exceed 40° C., and the activation is performed for 60-180 minutes; Step B, esterification specifically comprises: adding acetic anhydride and sulfuric acid to the activated system, controlling the temperature not to exceed 80° C., carrying out esterification, and then adding water to terminate the esterification reaction; preferably, step B, esterification specifically comprises: adding 300 to 500 parts by weight of acetic anhydride and 0.2 to 1 parts by weight of sulfuric acid to the activated system, controlling the temperature not to exceed 80° C., carrying out esterification until the appearance of the system gradually changes to a transparent colloid, and then adding 60 to 100 parts by weight of water to terminate the esterification reaction; Step E, precipitation and solidification specifically comprises: after the relay hydrolysis is completed, the system slurry is filtered, and then the filtrate is mixed with water, stirred, precipitated and solidified; preferably, step E, precipitation and solidification specifically comprises: after the relay hydrolysis is completed, the system slurry is filtered, and then the filtrate temperature is reduced to 10-30° C., and mixed with low-temperature water of 2-10° C., stirred, precipitated and solidified; Step F, post-treatment specifically includes: washing the solidified material with water until it is neutral, draining and drying, and obtaining cellulose acetate; preferably, step F, post-treatment specifically includes: washing the solidified material with water until it is neutral, draining and drying, and grinding it to a particle size not exceeding 500 μm to obtain cellulose acetate powder.

5. The method for preparing seawater-degradable cellulose acetate according to claim 1, characterized in that: In step F, the metal salt M is introduced x A y and / or metal oxide M z O w Operation; M x A y is a carbonate, bicarbonate or hydrochloride formed by any one of magnesium ion, calcium ion or barium ion, M x A y pK b The value is 3.7~7.6; M z O w An oxide formed by any one of magnesium, calcium or barium; Step F, post-treatment is specifically: washing the solidified material with water to neutrality, introducing metal salt M x A y and / or metal oxide M z O w After draining and drying, cellulose acetate is obtained; the metal salt M is introduced x A y and / or metal oxide M z O w The method is: a. Soaking: Soak the washed neutral material in the metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt M x A y and metal oxide M z O w or, b. washing: washing the neutralized material with a metal salt M x A y Aqueous solution, metal oxide M z O w Aqueous solution or metal salt M x A y and metal oxide M z O w Mix the aqueous solutions for washing.

6. The method for preparing seawater-degradable cellulose acetate according to claim 5, characterized in that: At least one of the following is met: In step F, the metal salt M x A y At least one selected from magnesium carbonate, calcium carbonate, barium carbonate, magnesium bicarbonate, calcium bicarbonate or barium bicarbonate; preferably, the metal salt M x A y At least one selected from magnesium carbonate or magnesium bicarbonate; In step F, the metal oxide M z O w At least one selected from magnesium oxide, calcium oxide or barium oxide; preferably, the metal oxide M z O w Selected from magnesium oxide; In step F, the metal salt M x A y The mass concentration of the aqueous solution is 10-40%, and the metal oxide M z O w The mass concentration of the aqueous solution is 10-40%, and the metal salt M x A y and metal oxide M z O w The mass concentration of the mixed aqueous solution is 10 to 40%; In step F, when the immersion method is adopted, the metal salt M in each aqueous solution is controlled x A y and metal oxide M z O w The total amount of the metal salt M in each aqueous solution is 0.1 to 1.0 parts by weight. x A y and metal oxide M z O w The total amount added is 0.1 to 0.5 parts by weight; In step F, when the immersion method is adopted, the immersion time is not less than 5 minutes; In step F, when washing is adopted, the amount of each aqueous solution is 0.5 to 5 parts by weight; In step F, cellulose acetate is ground to a particle size not exceeding 500 μm to obtain cellulose acetate powder.

7. The method for preparing seawater-degradable cellulose acetate according to claim 1 or 5, characterized in that: Also includes step G: Step G, melt processing: the cellulose acetate powder and the plasticizer are mixed evenly and fully plasticized, and then melt-extruded and granulated to obtain cellulose acetate granules.

8. The method for preparing seawater-degradable cellulose acetate according to claim 7, characterized in that: At least one of the following is met: In step G, the plasticizer is at least one of phthalates, glycerol lipids, citrate esters or polymerized polyols; preferably, the plasticizer is at least one of glycerol lipids, citrate esters or polymerized polyols; more preferably, the plasticizer is at least one of triethyl citrate, triacetin or PEG400; In step G, the amount of the plasticizer added is 20 to 40 parts by weight; In step G, the temperature of the melt extrusion granulation is set as follows: conveying section 80-170°C; melting section: 170-190°C; homogenization section: 170-200°C; die head: 200-220°C.

9. The seawater-degradable cellulose acetate prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The seawater-degradable cellulose acetate has a combined sulfonic acid group content of 20 to 200 ppm and a degree of substitution of 1.6 to 2.2; preferably, the seawater-degradable cellulose acetate has a combined sulfonic acid group content of 80 to 150 ppm and a degree of substitution of 1.7 to 2.

0.

10. Use of the seawater-degradable cellulose acetate prepared by the preparation method according to any one of claims 1 to 8 or the seawater-degradable cellulose acetate according to claim 9 in textiles, cigarette filters, cosmetics, mirror frames, packaging, cutlery, tool handles or medical drugs.

Citation Information

Patent Citations

  • New application of metal salt and method for improving stability of cellulose acetate

    CN108948214A

  • New uses of metal salts and methods to improve the stability of cellulose acetate

    CN108948214B

  • Cellulose acetate and cellulose acetate composition

    US20220267574A1

  • Cellulose ester compositions and shaped articles

    US5804296A